Towards an Inclusive Model of African Regional Integration: How Effective has the Linear Model been so Far? - Muzee, Hannah; Enaifoghe, Andrew Osehi (Journal of Economics and Behavioral Studies, 2019)
Abstract: The proponents of African regional integration hoped to create large economic spaces that allow economies of scale, increased efficiency, competitiveness and faster growth of Africa states. Whereas the linear model of regional integration seemed to have worked for the European Union, many have questioned its applicability in the African context. The applicability of the Linear model at the stages of Regional Economic Communities (RECs) like the EAC has met with significant stagnation primarily because of some bottlenecks such as poor infrastructure that limits the connectivity with the continent and lack of political will out of fear for the loss of sovereignty. The question thus lies in how the dream for a regionally united Africa will arise when its people cannot move and interact freely within the continent? By utilizing a secondary research design, this paper, therefore, sought to not only examine the effectiveness of the linear model of regional integration for Africa but also explore the possibility of incorporating the functionalist and federalist approach into an inclusive model for African regional integration. In examining the economic dynamics of regional integration, the paper identifies the benefits of economic integration, such as larger markets as a result of free movement of people and goods that could be harnessed by trading communities within Africa. Thus, the central argument in this paper does not discard the benefits and successes of the linear model of regional integration but concludes that its effectiveness can be enhanced by incorporating functionalist and at later stages federalist approaches to regional integration in Africa. The principal argument is that political and elitist integration agreements are futile when the continent is not connected physically and trade wise.